Protestant politics beyond Calvin : reformed theologians on war in the sixteenth and seventeenth centuries /: reformed theologians on war in the sixteenth and seventeenth centuries. (2022) - Campbell, Ian; Verhaart, Floris B (Floris Bart), 1988-
No abstract available